Sociodemographic factors related to handgrip strength in children and adolescents in a middle income country : The SALUS study (2017)
Objective To determine sociodemographic factors associated with handgrip (HG) strength in a representative sample of children and adolescents from a middle income country. Methods We evaluated youth between the ages of 8 and 17 from a representative sample of individuals from the Department of Santander, Colombia. Anthropometric measures, HG strength, and self‐reported physical activity were assessed, and parents/guardians completed sociodemographic questionnairres. Multinomial logistic regression models were used to estimate the association between sociodemographic and anthropometric characteristics and tertiles of relative HG strength. We also produced centile data for raw HG strength using quantile regression. Results 1,691 young people were evaluated. HG strength increased with age, and was higher in males than females in all age groups. Lower HG strength was associated with indicators of higher socioeconomic status, such as living in an urban area, residence in higher social strata neighborhoods, parent/guardian with secondary education or higher, higher household income, and membership in health insurance schemes. In addition, low HG strength was associated with lower physical activity levels and higher waist‐to‐hip ratio. In a fully adjusted regression model, all factors remained significant except for health insurance, household income, and physical activity level. Conclusions While age and gender specific HG strength values were substantially lower than contemporary data from high income countries, we found that within this middle income population indicators of higher socioeconomic status were associated with lower HG strength. This analysis also suggests that in countries undergoing rapid nutrition transition, improvements in socioeconomic conditions may be accompanied by reduction in muscle strength.